A Capillary Zone Electrophoresis Method with Multiresponse Chemometric Optimization for the Simultaneous Determination of Zofenopril Calcium and Hydrochlorothiazide in Presence of Hydrochlorothiazide Major Impurities. (15th March 2018) - Fayed, Ahmed S; Rezk, Mamdouh R; Marzouk, Hoda M; Abbas, Samah S
Abstract: In the present decade, great importance has been focused on the development of green analytical methods (GAM) as eco-friendly techniques. Minimizing the wastes, analysis time, hazardous reagents, sample size and energy are the main important principles for development of GAM. This manuscript describes a green, novel, rapid, accurate and reliable capillary zone electrophoresis method (CZE) for the simultaneous separation and determination of zofenopril calcium (ZOF) and hydrochlorothiazide (HCT) in presence of two major impurities of HCT, namely; chlorothiazide (CT) and salamide (DSA). Uncoated fused-silica capillary (50 μm i.d. × 48.5 cm and 40 cm effective length) was used. The main factors affecting the separation were the buffer concentration, pH of the buffer and applied voltage. Optimization of the experimental conditions was performed by applying response surface methodology (RSM). The experiments were designed using central composite face-centered design (CCD). The model obtained from the design described the linear, non-linear and interaction effects of factors on the responses. The optimum conditions given by the design were running buffer of sodium borate (pH 9.15; 10 mM) and 17 kV as positive mode applied voltage. Upon applying these conditions, baseline separation for the four compounds with short analysis time of 5.0 min was achieved. UV detection was performed at 225.0 nm and the capillary temperature was maintained at 25°C. The method was validated and applied for quantitative determination of the studied drugs according to the International Conference on Harmonization (ICH) guidelines. Good linearity was obtained in the range of 10.0–100.0 μg/mL for both ZOF and HCT. As for CT and DSA (HCT impurities), linearity range was 5.0–100.0 μg/mL. The proposed method was successfully applied for the analysis of these drugs in their synthetic mixtures and in their co-formulated pharmaceutical formulations.